Hubungan Status Pendidikan Kejadian Stunting pada Balita di Desa Petirhilir Baregreg Kabupaten Ciamis - Dini Ariani; Resna Litasari; Hani Septiani (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Stunting is used to describe a population of children who are too short in age. It is a sign that children are not developing well physically or psychologically, especially in the first 1000 days of life. The purpose of this study was to determine the relationship between the education of toddler mother and the incidence of stunting in children under five in Petirhilir Village, Ciamis Regency. This research used quantitative analytic research, retrospective method with a case control study design. The population in this study were all mothers who have toddlers aged 24–60 months. Sampling in this study using a technique using purposive sampling as many as 40 people. The results showed that most of the children who were stunted (42.5%) had low levels of education. The results of statistical analysis showed that maternal education had a significant relationship with the incidence of stunting as evidenced by a p-value